Bioaktivitas Ekstrak Daun Keladi Birah (Alocasia indica Schott) Terhadap Larva Udang A. salina LEACH Dengan Metode Brine Shrimp Lethality Test (BSLT) - Ivan Satria K.P.; Herman Herman; Muhammad Amir Masruhim (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2016)
Has done research Bioactivity Of Extract of Keladi Birah’s Leaf (Alocasia indica Schott) Against A. salina Leach Larvae Using Brine Shrimp Lethality Test Method. The purpose of this research to know bioactivity of keladi birah’s leaf against A. salina Leach larvae. Bioactivity of keladi birah’s leaf extract can view from the decease of A. salina Leach larvae ,then that been counted with Reed and Muench table. LC50 value of each crude extract methanol, n-hexane fraction, ethyl acetate fraction and n-butanol fraction was 68,86 ppm, 25,80 ppm, 20,89 ppm and 21,33 ppm. The resulted of brine shrimp lethality test showed that the keladi birah’s leaf is a bioactivity against A. salina Leach larvae.